The levels of testosterone, zinc, manganese and selenium in type 2 diabetic patient in South-Eastern Nigeria - Onah, Christian Ejike; Meludu, Samuel C.; Dioka, Chudi E.; Nnamah, Nwakasi K.; Nnoli, John Kennedy; Amah, Ubuo K.; Atuegbu, Chidiadi M.; Asuoha, Chika P. (International Journal of Research in Medical Sciences, 2017)
Background: This study is aimed at evaluating the levels of some trace elements and testosterone, and to ascertain their possible association in type 2 diabetes mellitus. Methods: Ninety male type 2 diabetic subjects and forty five apparently healthy non-diabetic male individuals were recruited into this study. The control group was matched for age with the study subjects and they were all within the age range of 30-67 years. Fasting Plasma Glucose (FPG), testosterone, trace elements (zinc, selenium, manganese), Body Mass Index (BMI) were determined. Results: This study showed significant decreases in the levels of trace elements (Zn, Se, and Mn) with a concomitant decrease in the levels of testosterone in type 2 diabetic patients (P <0.001). This findings were further strengthened by the strong positive correlation between testosterone and these trace elements (P <0.05). Conclusion: This suggests that low testosterone level might be as a result of low trace elements considering their role in testosterone production. Therefore, trace elements supplementation is recommended.